Comparison of gene flow among species that occur within the same geographic locations versus gene flow among populations within species reveals introgression among several Elymus species. Issue 2 (29th September 2015) - Wu, Pan‐Pan; Zuo, Hong‐Wei; Sun, Genlou; Wu, De‐Xiang; Salomon, Bjorn; Hu, Qun‐Wen; Dong, Zhao‐Rong
Abstract: One of the challenges in evolutionary biology is to understand the evolution of speciation with incomplete reproductive isolation as many taxa have continued gene flow both during and after speciation. Comparison of population structure between sympatric and allopatric populations can reveal specific introgression and determine if introgression occurs in a unidirectional or bidirectional manner. Simple sequence repeat markers were used to characterize sympatric and allopatric population structure of plant species, Elymus alaskanus (Scribn. and Merr.) Löve, E. caninus L., E. fibrosus (Schrenk) Tzvel., and E. mutabilis (Drobov) Tzvelev. Our results showed that genetic diversity ( H E ) at species level is E. caninus (0.5355) > E. alaskanus (0.4511) > E. fibrosus (0.3924) > E. mutabilis (0.3764), suggesting that E. caninus and E. alaskanus are more variable than E. fibrosus and E. mutabilis . Gene flow between species that occurs within the same geographic locations versus gene flow between populations within species was compared to provide evidence of introgression. Our results indicated that gene flow between species that occur within the same geographic location is higher than that between populations within species, suggesting that gene flow resulting from introgressive hybridization might have occurred among the sympatric populations of these species, and may play an important role in partitioning of genetic diversity among and within populations. The migration rate from E. fibrosus to E. mutabilis is highest (0.2631) among the four species studied. Asymmetrical rates of gene flow among four species were also observed. The findings highlight the complex evolution of these four Elymus species.